Albert Watkins and Howard Watkins Family Genealogy Trip to Tennessee - Watkins, Howard::::::::: (1986)
Exie Neander, Howard Neander, Helen Greenfield and Estelle Kelsey in front of Chattanooga Choo-Choo train